Cognitive-Processing Bias in Chinese Student Teachers with Strong and Weak Professional Identity - Wang, Xin-qiang; Zhu, Jun-cheng; Liu, Lu; Chen, Xiang-yu (Frontiers in Psychology, 2017)
Professional identity plays an important role in career development. Although many studies have examined professional identity, differences in cognitive-processing biases between Chinese student teachers with strong and weak professional identity are poorly understood. The current study adopted Tversky’s social-cognitive experimental paradigm to explore cognitive-processing biases in Chinese student teachers with strong and weak professional identity. Experiment 1 showed that participants with strong professional identity exhibited stronger positive-coding bias toward positive profession-related life events, relative to that observed in those with weak professional identity. Experiment 2 showed that participants with strong professional identity exhibited greater recognition bias for previously read items, relative to that observed in those with weak professional identity. Overall, the results suggested that participants with strong professional identity exhibited greater positive cognitive-processing bias relative to that observed in those with weak professional identity.